The effects of parental support on students' academic achievement in English Language subject in secondary school / Nur Syafia Izzah Ismail - Ismail, Nur Syafia Izzah (Faculty of Education, 2014)
This study is conducted to examine the effects of parental support on students' academic achievement in English Language subject in secondary school. This study is carried out to examine the effects of parental support which the focus would be on the parents' socioeconomic status and parental involvement. By using the survey techniques, which is the questionnaire, 60 students from Sekolah Menengah Kebangsaan Pengkalan Chepa, Pengkalan Chepa, Kelantan were involved with this study as the respondents. These 60 respondents were all form three students from the best two classes at the school. This study showed that parents' socioeconomic status plays a very minor role in determining the students' academic achievement in English Language subject in secondary school. It also revealed that the parents' socioeconomic status plays a very minor role in determining how involved the parents are with their children's academic achievement in English Language subject in secondary school. The result of this study will change the teachers' perceptions as well as the way they see their students regardless of their socioeconomic status.